STG a tool for generating symbolic test programs and oracles from operational specifications. - Clarke, Duncan (Software engineering notes.)
We report on a tool we have developed that automates the derivation of tests from specifications. The tool implements conformance testing techniques to derive symbolic tests that incorporate their own oracles from formal operational specifications. It was applied for testing a simple version of the CEPS (Common Electronic Purse Specification).